Anterior Minithoracotomy vs. Transcatheter Closure of Patent Ductus Arteriosus in Very Preterm Infants - Lenoir, Marien; Wanert, Chloé; Bonnet, Damien; Méot, Mathilde; Tosello, Barthélémy; Fouilloux, Virginie; Ovaert, Caroline; Malekzadeh-Milani, Sophie (Frontiers in Pediatrics, 2021)
Introduction: Patent ductus arteriosus (PDA) is common in preterm infants and contributes to morbi-mortality. Several studies have shown the feasibility and safety of percutaneous PDA closure. Minimally invasive surgical ligation by anterior thoracotomy is an alternative, bedside technique for PDA closure in very low birth weight preterm infants. Our study aimed to compare short- and medium-term morbidity and mortality between anterior mini-thoracotomy and transcatheter PDA closure. Methods: From 2010 to 2020, 92 preterm infants < 1600 g underwent PDA closure in 2 centres: 44 surgical anterior mini-thoracotomies (centre 1) and 48 transcatheter closures (centre 2). Using a 1:1 propensity score match analysis, 22 patients in each group were included. The primary outcome was time to extubation after intervention. Results: Preoperative characteristics were similar in both groups after propensity matching (mean weight at procedure, 1171±183gr; p=0.8). Mean time to extubation was similar: 10±15 days in the surgical group versus 9±13 days in the transcatheter group (p=0.9). Mean age at hospital discharge was 114±29 days vs 105±19 days (p=0.2). Two deaths occurred in the surgical group and one in the transcatheter group (logRank=0.61). Five complications (pneumothorax n=2, chylothorax n=2, phrenic nerve injury n=1) occurred in 3 patients after surgery. Three complications (chylothorax n=1, endocarditis n=1, renal vein thrombosis n=1) occurred in 2 patients after percutaneous closure (p=0.63). Conclusion: Equivalent efficiency and safety of surgical mini-invasive vs transcatheter PDA closure in preterm infants <1600 g are in favour of applying these alternative techniques according to centres’ facilities and competences.